PENGARUH INVESTASI ASING TERHADAP PEREKONOMIAN INDONESIA - Nike Fiola; Aprilliantoni, Aprilliantoni (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Foreign Investment or Foreign Direct Investment (FDI) has a strategic role in supporting the progress of the Indonesian economy, especially in increasing the competitiveness of the national economy. The purpose of this study is to analyze the influence of Foreign Direct Investment (FDI) on various aspects of economic growth in Indonesia. Using a qualitative descriptive approach, this study reveals that FDI not only contributes to increasing production capacity, but also provides benefits in the form of technology transfer, job creation, and increasing the competitiveness of local industries. The data obtained shows that throughout 2024, investment realization in Indonesia reached IDR 829.9 trillion, of which FDI contributed 50.7% or around IDR 421.7 trillion. Meanwhile, Domestic Direct Investment (FDI) recorded higher growth of 29.1% annually. Investment equity outside Java also recorded significant growth of 18.3%, indicating the government's success in encouraging equitable economic development. However, the success of this investment requires attention to aspects of ethics, desire, and the principle of transparency to support inclusive and sustainable economic growth.